2004
DOI: 10.1002/mats.200300011
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Caustic Addition in Epoxy Polymerization Process: A Single and Multi‐Objective Evolutionary Approach

Abstract: Summary: An epoxy polymerization process is studied in semi‐batch mode. Caustic has a very critical influence on epoxy polymerization process, which is modeled as a set of highly nonlinear coupled ODE's (ordinary differential equations). Owing to the highly complicated, nonlinear domain of analysis, “Differential Evolution (DE)” and “Genetic Algorithm (GA)” are used as optimization tools to identify the $\overline M _{\rm n}$‐PDI Pareto set and study the best operating strategy with respect to NaOH addition. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 14 publications
0
22
0
Order By: Relevance
“…Given two discrete profiles of addition of reactants (the entire U at various time points) and initial conditions of all state variables (x at time zero), the complete mathematical model can be solved by using an explicit integrator (a RK type method proposed by Walas [12] is used here). While applied to many other numerical textbook examples and in Raha et al [9,10] , this explicit integrator method proves its strength for all the cases even with a case like 48 strongly coupled non-linear ODEs. The kinetic parameters appearing in the model equations are estimated from the available experimental data from Karayannidis et al [1] using simple genetic algorithms (SGA).…”
Section: Kinetic Analysis and Optimization For The Catalytic Esterifimentioning
confidence: 96%
“…Given two discrete profiles of addition of reactants (the entire U at various time points) and initial conditions of all state variables (x at time zero), the complete mathematical model can be solved by using an explicit integrator (a RK type method proposed by Walas [12] is used here). While applied to many other numerical textbook examples and in Raha et al [9,10] , this explicit integrator method proves its strength for all the cases even with a case like 48 strongly coupled non-linear ODEs. The kinetic parameters appearing in the model equations are estimated from the available experimental data from Karayannidis et al [1] using simple genetic algorithms (SGA).…”
Section: Kinetic Analysis and Optimization For The Catalytic Esterifimentioning
confidence: 96%
“…Raha, Majumdar and Gupta [17] have validated the model with the available experimental data. Using the species balance approach, ODEs corresponding to the initial value problem (IVP) are derived for various species and their moments.…”
Section: Problem Formulationmentioning
confidence: 94%
“…They gave special importance to build the entire modeling framework as well as the effect of kinetic parameters and reactant's effect over the performance of the reaction process. However, based on some earlier studies [17] which showed the importance of all three reactants, we launch the present detail study for a better understanding of the true nature of interactions among three conflicting objectives associated in an epoxy polymerization process.…”
Section: Introductionmentioning
confidence: 99%
“…They have estimated the kinetic parameters from available experimental data through a simple genetic algorithm (SGA). Raha et al [7] also examined the effect of NaOH on the pareto optimal (PO) solutions while simultaneously maximizing the number average molecular weight (M n ) and minimizing the polydispersity index (PDI) for a targeted product quality, amount of added NaOH at different time steps being the decision variables. Optimum NaOH addition profiles is identified and demonstrated through case studies.…”
Section: Introductionmentioning
confidence: 99%